Postprandial hyperlipidemia as a coronary atherosclerosis factor in patients with metabolic syndrome; corrective potential of rosuvastatin therapy - T. V. Krovyakova; P. A. Lebedev (Кардиоваскулярная терапия и профилактика)
Aim. To investigate the atherogenic role of postprandial hyperlipidemia (PPH) and endothelial dysfunction (ED) in the development of coronary angiosclerosis in patients with coronary heart disease (CHD) and metabolic syndrome (MS); to study the effectiveness of rosuvastatin in the correction of these factors. Material and methods. The first study phase included 18 CHD and MS-free participants (control group, CG) and 52 patients with CHD and MS. Based on the coronary angiography (CAG) results, the patients with CHD and MS were divided into 2 groups: Group I (n=27) with moderate coronary artery (CA) stenosis (1-4 points), and Group II (n=25) with severe CA stenosis (5-16 points). All participants received a standard lipid load (LL), and peripheral artery reactivity was assessed by photoplethysmography at fasting state and 6 hours after LL. The second study phase included 21 patients with CHD and MS, to investigate the effects of rosuvastatin (10 mg/d) on fasting and PPH and ED. Results. The results of the first study phase demonstrated that in controls and patients with CHD and MS, LL resulted in different types of PPH. In Groups I and II, but not in controls, substantial and long-lasting PPH manifested in increased levels of triglycerides (TG) and low-density lipoproteins (LDL), as well as in decreased levels of high-density lipoproteins (HDL). In addition, decreased endothelial function (EF) was observed in all three groups, with vasospastic reaction in Groups I and II. Rosuvastatin therapy improved the fasting and postprandial levels of total cholesterol (TCH), TG, LDL, and also improved endothelium-dependent vasodilatation 6 hours after LL. Conclusion. PPH phenomenon is characterised by high atherogenic potential and linked to peripheral artery ED and coronary angiosclerosis. Photoplethysmography is a non-invasive, reliable method for identifying the patients with severe CA stenosis. Rosuvastatin therapy (10 mg/d) improves fasting and postprandial lipid levels, as well as postprandial EF.